1993
DOI: 10.3147/jsfp.28.171
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus cyprini: Thermal Effects on Pathogenicity and Oncogenicity.

Abstract: Effects of thermal conditions on CHV infection were investigated both in vitro and in vivo. CHV multiplied in FHM cells at incubation temperatures from 10•Ž to 25•Ž, but not at 30•Ž, optimal temperature being 15-20•Ž. Experimental infection of CHV was done on carp fry under controlled water temperatures of 15, 20 and 25•Ž. The mortality of carp fry due to CHV infection was markedly high at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…For instance, latent CyHV-1 persists in carp that survive infection (41), and AngHV-1 persists in surviving infected eels (38,47). In these cases, the viral genome was found in cranial nerve cells and spinal nerves by using in situ hybridization (31,41,42). It would be interesting to determine whether the pathogenic and attenuated CNGV and CyHV-2 also persist in nerves of survivors.…”
Section: Latencymentioning
confidence: 99%
“…For instance, latent CyHV-1 persists in carp that survive infection (41), and AngHV-1 persists in surviving infected eels (38,47). In these cases, the viral genome was found in cranial nerve cells and spinal nerves by using in situ hybridization (31,41,42). It would be interesting to determine whether the pathogenic and attenuated CNGV and CyHV-2 also persist in nerves of survivors.…”
Section: Latencymentioning
confidence: 99%
“…Unfortunately, no water-quality data are available for that period. The role of rising water temperature to papilloma outbreak is not likely, since Sano et al (1993) found a regression of papillomatosis induced by Herpesvirus cyprini in rising water temperature in fancy carp Cyprinus carpio.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no water-quality data are available for that period. The role of rising water temperature to papilloma outbreak is not likely, since Sano et al (1993) found a regression of papillomatosis induced by Herpesvirus cyprini in rising water temperature in fancy carp Cyprinus carpio.Roach males produce breeding tubercles during spawning. Breeding tubercles are keratinised epidermal nodules, which are found commonly in many fish taxa, more often in males (see review in Wiley & Collette 1970).…”
mentioning
confidence: 99%
“…Such papillomas coalesce as they spread over the surface of carp as white plaques, and develop focal exophytic masses (Wildgoose, 1992). These papillomas are caused by Herpesvirus cyprini (also cyprinid herpesvirus 1, CHV) (Sano et al, 1991), regress in warm summers or when held above 20°C (Sano et al, 1993b), and persist below 15°C (Sano et al, 1993a). Viruses have also been associated with papillary epidermal plaques in other fish species (Wolf, 1988), such as walleye, in which a retroviral etiology is suspected (LaPierre et al, 1998).…”
Section: Beckwith Et Almentioning
confidence: 99%